Matrix metalloproteinase-3 levels in relation to disease activity and radiological progression in rheumatoid arthritis - Tuncer, Turkan; Kaya, Arzu; Gulkesen, Arif; Kal, Gul Ayden; Kaman, Dilara; Akgol, Gurkan (Wroclaw Medical Univ, 2019)
Background. Rheumatoid arthritis (RA) is a chronic inflammatory and systemic disease of unknown etiology that primarily affects synovial joints and involves progressive destruction around the joints. Inflammation starting in the joint synovium causes the destruction of cartilage, bone and other adjacent tissues with pannus formation. Objectives. The aim of this study was to evaluate serum matrix metalloproteinase-3 (MMP-3) levels and their clinical and radiological significance in patients with rheumatoid arthritis. Material and methods. The study included 59 patients with RA and 30 healthy controls. Serum MMP-3 levels were measured using the enzyme-linked immunosorbent assay (ELISA) method. Patients with a Disease Activity Score 28 (DAS28) <= 3.2 were categorized as having lower disease activity, while a DAS28 score > 3.2 indicated patients with moderate/high disease activity. Additionally, the patients were divided into 2 groups in terms of disease duration: early RA (disease duration <= 2 years) and established RA (disease duration <= 2 years). Functional disability was evaluated using the Health Assessment Questionnaire (HAQ) and Nottingham Health Profile (NHP). Radiographs were scored using modified Larsen scoring. Results. Serum MMP-3 levels in patients with RA were significantly higher than in controls (p = 0.001). Serum MMP-3 levels were correlated with laboratory and clinical parameters of disease activity, including erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), DAS28, and HAQ score; the exceptions were rheumatoid factor (RF) and cyclic citrullinated peptides (CCP). The serum MMP-3 levels of RA patients with moderate/high disease activity were found to be significantly higher than those of the patients with low disease activity (p < 0.001). However, MMP-3 levels were found to be similar in both established and early RA patients (p = 0.927). Additionally, the modified Larsen scores, which indicate structural damage, correlated significantly with serum MMP-3 levels (p = 0.001). Conclusions. These results indicate that serum MMP-3 levels may be used as an indicator for structural damage such as erosions in the early stages of the disease, and to monitor disease activity.
Keywords: rheumatoid arthritis; matrix metalloproteinase 3; disease activity; modified Larsen score